Trade-off analysis between global impact potential and local risk: A case study of refrigerants. (20th April 2019) - Xue, Mianqiang; Kojima, Naoya; Zhou, Liang; Machimura, Takashi; Tokai, Akihiro
Abstract: Refrigerants can have potential adverse impacts on human health through their life cycles at a global scale. However, they may also lead to a health risk because of direct exposure at a local scale. A policy intervention aiming to reduce one effect might simultaneously affect another. To address risk transfer or transformation, the present study evaluated both the global impact potential and local risk of refrigerants used in household air conditioners using methods based on life cycle assessment (LCA) and risk assessment (RA). LCA results indicated that human health damage attributable to energy consumption was greater than that attributable to refrigerant emission. The former was dominated by the use phase while the latter was dominated by the disposal phase. RA results indicated that the margin of exposure of R-22, R-410a, and R-32 were greater than 10 6 . When R-22 was replaced with R-410a, we identified a trade-off between local risk and global warming potential (also between ozone depletion potential and global warming potential) because of refrigerant emission. This study is a real-world synergistic application of LCA and RA. Complimentary application of these two approaches could contribute to broad decision making in green product development by employing a systemic view and transcending disciplines. Highlights: The global impact potential of refrigerants was estimated by life cycle assessment. The local risk of refrigerants was evaluated by risk assessment. We conducted trade-off analysis based on scenario modeling. The broad outcomes can contribute to a more robust decision making.